Fuel ion ratio determination in NBI heated deuterium tritium fusion plasmas at JET using neutron emission spectrometry. (14th January 2015) - Hellesen, C.; Eriksson, J.; Binda, F.; Conroy, S.; Ericsson, G.; Hjalmarsson, A.; Skiba, M.; Weiszflog, M.
Abstract: The fuel ion ratio ( n t / n d ) is of central importance for the performance and control of a future burning fusion plasma, and reliable measurements of this quantity are essential for ITER. This paper demonstrates a method to derive the core fuel ion ratio by comparing the thermonuclear and beam-thermal neutron emission intensities, using a neutron spectrometer. The method is applied to NBI heated deuterium tritium (DT) plasmas at JET, using data from the magnetic proton recoil spectrometer. The trend in the results is consistent with Penning trap measurements of the fuel ion ratio at the edge of the plasma, but there is a discrepancy in the absolute values, possibly owing to the fact that the two measurements are weighted towards different parts of the plasma. It is suggested to further validate this method by comparing it to the traditionally proposed method to estimate n t / n d from the ratio of the thermal DD and DT neutron emission components. The spectrometer requirements for measuring n t / n d at ITER are also briefly discussed.